Applying of teaching strategy based on cognitive load theory to develop pre-service teacher teaching skills of waves: Cognitive load analysis. Issue 2 (February 2019) - Permana, I; Firman, H; Redjeki, S; Hamidah, I
Abstract: This study aimed to reveal Pre-Service Teacher's cognitive load representing the effectiveness of teaching strategy based on cognitive load theory. Cognitive load is described as correlation among Intrinsic Cognitive Load (ICL) and Extraneous Cognitive Load (ECL). Teaching strategy was developed by Cognitive load Theory with the stages such as Introduction, Reflection, Visualization, Application, Recitation, and Evaluation. Participants in the study were 31 pre-service science teachers in Bogor and Bandung Indonesia. Data of ECL were collected with a complexity task containing a short question to measure the ability of information analysis during lecturer. ECL data were collected with a 7-scale questionnaire contains a statement of the mental effort of pre-service science teachers in lecturer. Result of data analysis found that applied lecture strategy successfully improved pre-service science teachers ICL and reduce ECL. This strategy produced low mental effort especially at introduction stage. The mental effort increases on the application stage.